2014
DOI: 10.1002/pc.23209
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and microwave absorbing characteristics of flake‐like polypyrrole filled composites in X‐band

Abstract: Polypyrrole (PPy)/montmorillonite (MMT) nanocompounds were prepared by in situ chemical oxidative polymerization of pyrrole in the presence of MMT. The results indicate PPy is intercalated into MMT interlayers and the morphology of obtained PPy in nanocompounds is changed to flake-like rather than granular particles as pristine PPy. The resultant PPy/ MMT nanocompounds and pristine PPy were used as microwave absorbing filler separately to prepare microwave absorbing PPy/MMT and PPy epoxy composites. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The microwave absorbing property by the material depends on the dielectric and magnetic loss. The magnetic resonance inside the polymer composite may be due to natural and exchange resonance [11]. Figure 3(a) shows the graph for dielectric and magnetic loss.…”
Section: Electromagnetic Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…The microwave absorbing property by the material depends on the dielectric and magnetic loss. The magnetic resonance inside the polymer composite may be due to natural and exchange resonance [11]. Figure 3(a) shows the graph for dielectric and magnetic loss.…”
Section: Electromagnetic Parametermentioning
confidence: 99%
“…Microwave absorbing materials should be light weight, chemically and environmentally stable and low density. Jin et al synthesized PPy/MMT polymer composite, which has the microwave absorbing power of −10 dB at X-band frequency [11]. Tiwari [12] et al developed a simple differential bridge technique to measure the dielectric constant of thin polymer film of PPy and polystyrene at microwave range.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsically conducting polymers (ICP's), such as polypyrrole (PPy) and polyaniline (PANI), have been used as conductive filler to produce CPC's (Moučka et al, 2011;Jin et al, 2016;Merlini et al, 2017;Ramoa et al, 2018). Considerable efforts have been made in order to improve the dispersion of ICP's into the matrix and to reduce the amount of the filler necessary to achieve high values of electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been made in order to improve the dispersion of ICP's into the matrix and to reduce the amount of the filler necessary to achieve high values of electrical conductivity. Works in literature have reported that the synthesis of PPy into layered inorganic host material, such as, montmorillonite (Mt), results in nanostructured conductive filler of Mt/PPy, with an intercalative or exfoliated structure, large surface area, and high electrical conductivity (Moučka et al, 2011;Jin et al, 2016;Merlini et al, 2017;Ramoa et al, 2018). The chemical in situ polymerization has been the most studied method for the production of Mt/PPy nanostructured conductive filler.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent EMI and increase the device efficiency and lifetime, many studies have been focused in producing electromagnetic radiation shielding or absorbing materials. In this context, electrically conducting polymer composites composed of intrinsically conducting polymer (ICP), such as polypyrrole (PPy) and polyaniline (PAni), dispersed in an insulating polymer matrix have attracted much interest for EMI shielding applications . The scientific and technological interest for producing these materials is due to their lightweight, corrosion resistance, design flexibility, good processability, physical properties of polymeric materials, high electromagnetic interference shielding effectiveness (EMI SE), and good microwave absorption properties .…”
Section: Introductionmentioning
confidence: 99%